Collected essays. Volume V, Religion and public reasons - Finnis, John. (Oxford : Oxford University Press, 2011)
This volume collects the theological work of John Finnis spanning his contribution to such foundational issues as the justification for belief in revelation and moral-theological methodology and the role of religion in public reason and law.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Natural law; Natural law -- Religious aspects